The atheism of modern philosophers – selected forms = Ateizm współczesnych filozofów – wybrane postacie - Drozdowicz, Zbigniew (Przegla̜d religioznawczy, 2020)
In these remarks once again (this problem had occurred already in ancient times) I take on the issue of atheism of philosophers. In this case I’m interested in those modern philosophers who combined their own philosophical thought with doing one of particular scientific disciplines. Some of them (like Victor J. Stenger for example) are more recognized as distinguished scholars, however some (like Daniel Dennett for example) as scholars and atheists, and others as atheists (like Michel Onfray and Michael Ruse). From the point of view of contemporary debates on atheism it is important to show how they joined their own atheism with the theses of the sciences they recall in their works.